Life’s Too Short to be polite: Exploiting impoliteness and rudeness in Gervais And Merchant’s humour about physical difference (Altre Modernità, 2019)
What follows is a qualitative analysis of the use of impoliteness for comiceffect in the British comedy series Life’s Too Short written by Ricky Gervais and StephenMerchant. Because each episode centres on Warwick Davis, an actor with restrictedgrowth, or dwarfism, there is a considerable risk of superiority or disparagement-typecomedy about a taboo subject like physical difference, stigmatized in current Britishculture. In this analysis I set out to show that the authors’ use of impoliteness plays animportant role in allowing them to write comedy centred on this sensitive issue.The starting-point of the analysis is Culpeper’s proposal that impoliteness can beentertaining, which in this case is applied to scripted comedy rather than impromptuor semi-spontaneous examples of impoliteness for purposes of entertainment.Referring to aspects of impoliteness applied to entertainment, and with reference tothe concept of face, and to superiority, incongruity, and relief humour theories, thepaper suggests there are at least six techniques by which the authors use impolitenessto reprise physical difference for a contemporary comedy series.